The Feasible Gains from International Risk Sharing - Sylvester Eijffinger; Wolf Wagner (Center for Economic Studies and ifo Institute (CESifo), 2001)
We argue that since there are several impediments to international risk sharing, the welfare gains from full international risk sharing, which have been the object of analysis in the previous literature, are not suggestive. Instead, we study the gains from feasible risk sharing and find that they are considerable (0:5% increase inpermanent consumption). Marginal benefits from further risk sharing are low, which indicates that feasible risk sharing can achieve most of the benefits from internationalrisk sharing. Surprisingly, we find that sharing short term consumption risk lowers welfare. On the basis of the results we make suggestions on how to improve existing international risk sharing systems.
Keywords: F40; G15; 330; International risk sharing; welfare gains